Scattering and attenuation of surface acoustic waves in droplet actuation - Jiao, Z. J. (2012)
This paper presents an analytical model for surface acoustic waves (SAW) in actuating a single liquid droplet on a piezoelectric substrate. Both scattering waves outside the droplet and attenuation waves beneath the droplet are obtained, and the energy transfer from SAW to droplet in the process of actuation is calculated. The results from this analytical model can provide qualitative explanations to some experimental observations, such as the weak actuation behind the droplet and flow patterns inside the droplet. It is found that effective actuation wavelength is around 1/5 of the droplet radius, at which the droplet absorbs the maximum incident SAW energy.